MACI Sandwich Technique With Autologous Bone Graft - Tom Minas MD, MS (SAGE Publishing, 2024)
Background: Osteochondral lesions of the knee are difficult to manage. Such lesions can be effectively treated with the matrix-induced autologous chondrocyte implantation (MACI) "sandwich" technique using autologous chondrocytes on porcine collagen membrane in conjuction with autologous cancellous bone grafting (ABG). Few studies have examined this technique to restore the osteochondral unit. Indications: The MACI "Sandwich" procedure is indicated when osteochondral lesions are larger than 2 cm 2 in size and deeper than 8 to 10 mm, with symptoms consistent with the location of the lesion. Technique Description: The chondral defect is radically debrided back to healthy bone and cartilage tissue. The base of the bony cavity is drilled to enhance the vascular supply and promote healing. Next, the bony cavity is prepared to slightly undermine the subchondral bone surface around the articular margins, with the depth of the cavity wider than the opening, similar to a dental amalgam. The autologous cancellous bone is subsequently morselized and impacted up to the level of the native subchondral bone plate. The first MACI membrane with the cells facing up is placed directly onto the bone graft site and compressed with a neural patty. The neural patty is removed, and the second MACI membrane is then placed with the cells facing down. The edges are then micro-sutured to ensure stability. Results: The "sandwich" technique has superior survival rates compared with autologous bone grafting alone, with patients reporting decreased pain, improved function, and high satisfaction scores over a mid-term to long-term follow-up. Discussion/Conclusion: The MACI "sandwich" technique is an effective surgical intervention to restore the osteochondral unit and preserve the patient's native knee joint. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.